La estética de Kant y el problema del juicio estético en la música - Pascual, Luciano (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
This paper reconstructs the place of music in the division of the arts proposed by Kant in his third Critique, focusing on the aspects that make music an artdifficult to characterise. For this purpose, it exposes the foundations that allow situating music at the highest levels of Kant’s incipient system of the arts, as well as the reasons that allow placing it on the lowest ones. In addition, the paper approaches the problem of the pendular place of music as a beautiful art and as an agreeable art, recovering and contrasting different passages of Kant’s Critique of Judgement. To complement this last aim, readings from different thinkers are reviewed, considering, on the one hand, those who claim that Kant characterises music as a beautiful art, and, on the other hand, those who claim that he characterises it as a mere agreeable art. Finally, this paper presents the conclusions that allow to understand that music’s double possibility, as a beautiful and as agreeable art, depends on the ways in which the subject relates to music.

En este trabajo reconstruimos el lugar de la música en la división de las artes propuesto por Kant en su tercera crítica, deteniéndonos en los aspectosque la vuelven un arte complejo de caracterizar. Para este objetivo expondremos los fundamentos que permiten ubicar a la música en los lugares más elevados de su incipiente sistema de las artes, como también aquellas razones que permiten encontrarla dentro de los más bajos. Además, abordamos el problema del lugar pendular de la música como arte bello y como arte agradable, recuperando y contrastando diversos pasajes de su Crítica de la facultad de juzgar. Para complementar este último objetivo, recuperamos lecturas de diferentes pensadoras y pensadores encontrando, por un lado, a quienes consideran que Kant caracteriza a la música como arte bello, y por otro, a quienes consideran que la caracteriza como mero arte agradable. Finalmente presentamos las conclusiones que permiten comprender que su doble posibilidad, como arte bello y agradable, depende de las formas en las que el sujeto se vincula con la música.
Kant’s Aesthetics and the Problem of Aesthetic Judgement in Music
Keywords: Music; Kant; Division of arts; Música; Kant; División de las artes; https://purl.org/pe-repo/ocde/ford#6.03.01